Step activity monitoring to assess ambulation before and after total ankle arthroplasty - Assal, Mathieu; Che Ahmad, Aminudin; Lacraz, Alain; Courvoisier, Delphine S.; Stern, Richard; Crevoisier, Xavier (Elsevier Limited, 2011)
Background: The study objective was to compare walking activity before and after total ankle arthroplasty (TAA). Methods: Nineteen patients who underwent TAA were prospectively reviewed with a dedicated ambulatory activity-monitoring device. Patients were tested 1 month prior to surgery, and at least 18 months post-operative. Ambulatory parameters included number of steps at different cadences and time spent walking at different paces. The American Orthopaedic Foot and Ankle (AOFAS) hindfoot scale was assessed at similar intervals. Results: Following TAA, there was significant improvement in the number of steps walked at normal cadence, while importantly the number of steps walked at low and medium cadence decreased. There was no significant difference between the time actually spent walking at any cadence after arthroplasty. The mean AOFAS hindfoot scale significantly improved. Conclusions: Following TAA, patients show an improved walking pace and AOFAS hindfoot scale, but no difference in the amount of time spent walking. © 2010 European Foot and Ankle Society.